Evaluation of the Neotropical Stingless Bee Melipona quadrifasciata (Hymenoptera: Apidae) as pollinator of greenhouse tomatoes - Del Sarto, M.C.L.; Peruquetti, R. C.; Campos, L.A.O. (Journal of Economic Entomology, 2004)
The Neotropical stingless bee Melipona quadrifasciata Lepeletier was evaluated for pollinating tomatoes (variety Rodas; long-life hybrid) in greenhouses under plastic and with a hydroponic system and “organic concepts” in Minas Gerais State, Brazil. Flowers not pollinated did not set any fruit. Pollination by bees plus manual pollination did not differ from either bee or manual pollination. Maximum fruit diameter, fruit height, and roundness (quotient between maximum fruit diameter and fruit height) were not significantly different between treatments, but fruit visited by M. quadrifasciata had 10.8% less seeds (dry mass) than manual pollination. This apparently low efficiency of M. quadrifasciata pollination was attributed to the overlap of only 30 min between highest bee foraging activity and highest flower stigma receptivity. Thus, it was concluded that M. quadrifasciata is a feasible pollinator of greenhouse tomatoes because of 1) the observed increase in fruit quality with lower mechanical injury than traditional manual pollination, 2) no significant decrease in fruit size, and 3) high price of such product in the market. Some considerations for sustainable use of M. quadrifasciata as greenhouse pollinator are presented. Although techniques for keeping captive colonies of M. quadrifasciata are currently available, the sole current method for acquiring new colonies is removing them from the forest, and if demand was created for large numbers of colonies for commercial use, techniques for captive rearing must be developed to prevent serious declines in wild populations.

A abelha-sem-ferrão Neotropical Melipona quadrifasciata Lepeletier foi avaliada para a polinização de tomates hidropônicos (híbrido longa-vida variedade Rodas) em casas-de-vegetação sob plástico e com ‘conceitos orgânicos’ em Minas Gerais, Brasil. As flores não polinizadas não produziram frutos. A polinização pelas abelhas juntamente com a polinização manual não diferiu da polinização somente pela abelha ou somente manual. O diâmetro máximo e a altura dos frutos e sua circunferência (quociente entre o diâmetro máximo e a altura dos frutos) não foram significativamente diferentes entre os tratamentos, mas os frutos visitados por M. quadrifasciata apresentaram 10,8% menos sementes (peso seco) do que os polinizados manualmente. Esta eficiência aparentemente baixa de M. quadrifasciata como polinizador foi atribuída à sobreposição de apenas 30 min entre o pico máximo de forrageamento das abelhas e a maior receptividade do estigma das flores. Concluiu-se ser possível usar M. quadrifasciata como polinizador de tomates cultivados em casa-de-vegetação porque (i) houve aumento na qualidade dos frutos, considerando-se a diminuição das injúrias mecânicas quando comparada à polinização manual tradicional, (ii) não houve diminuição do tamanho do fruto e (iii) pelo alto preço deste produto no mercado. Algumas considerações sobre o uso sustentável de M. quadrifasciata como polinizador em casas-de-vegetação são apresentadas. Apesar de existirem técnicas para manter colônias de M. quadrifasciata em cativeiro, o único método para aquisição de novas colônias e a retirada delas da mata e, criando-se demanda por grande número delas para uso comercial, técnicas de criação em cativeiro necessitam ser desenvolvidas, o que poderia prevenir grandes declínios das populações naturais desta abelha.
Keywords: Greenhouse pollination; Lycopersicon; Protected cultivation; Stingless bee